Challenges for high performance and very low power operation at the end of the Roadmap. (May 2019) - Balestra, Francis
Highlights: New materials and novel device architectures. End of the Roadmap. Multigate NanoCMOS and Nanowire FET. Small slope switches Tunnel FET and FE-FET. Hybrid nanoscale transistors. Alternative materials ultra-thin Si-Ge-III-V/OI, 2D, 1D, Heterostructures. Abstract: Future Nanoelectronic devices faces substantial challenges, in particular increased power consumption, saturation of performance, large variability and reliability limitation. In this respect, novel materials and innovative device architectures will be needed for Nanoscale FETs. This paper presents some promising solutions for the end of the roadmap with Multigate Nanodevices, Nanowires, Tunnel transistors, Ferroelectric FET, and Hybrid Nanocomponents using Phase Change materials or nanofilament. Other alternative materials, as ultra-thin films, 2D and 1D nanostructures, Heterostructures using strained or III-V materials, will also allow to boost these advanced nanotransistors.